THE ATMOSPHERIC ELEMENTS OF THE EGYPTIAN MUSEUMS AND THEIR EFFECT ON THE EGYPTIANS' INTENTIONS TO REVISIT - Radwa GAMAL; Jermin ABDELKAFY; Dalia SOLIMAN (Geo Journal of Tourism and Geosites, 2023)
This study aims to fill the salient gap in the area of museums' atmospheric elements by examining their effect on the Egyptian visitors’ behavioral outcomes and the resulting effect on their intention to revisit the museum. An online questionnaire was distributed to a convenient sample of the Egyptian museums' visitors (346 respondents) to gather and analyze primary data along with analyzing the secondary data (literature). The results confirmed that museum's atmospheric elements have a positive and significant effect on the visitors’ experiences. This resulted in positive behavioral outcomes that consequently affected the Egyptian visitors’ intention to revisit the museum. This study investigates the importance of taking the physical design and atmospheric elements into consideration by the museum curators and managers, especially during the current phase in Egypt where various museum renewals and constructions are being held.